Comparative Small RNA Profiling and Functional Exploration on Wheat With High- and Low-Cadmium Accumulation - Liu, Yuqing; Wang, Xudong; Yuan, Leyi; Liu, Yuxiang; Shen, Tong; Zhang, Yunhua (Frontiers in Genetics, 2021)
Cadmium is a toxic metal widely distributed in workplaces and plant soils due to extensive industrialization. Wheat is one of the most important sources of food generated from plant soils. The different responses of wheat against cadmium different omics levels have been observed and widely studied worldwide. With the development of high-throughput sequencing, micro-level biological research has extended to the microRNA level. In this study, high-cadmium accumulation wheat cultivars Annong9267 and low-cadmium accumulation wheat cultivars Qian 102032 were used as experimental models. The two cultivars were treated by Cd for 2 hours, to explore the microRNA profiles in root and leaf tissues through small RNA sequencing. Important small RNAs such as tae-miR9663-5p and tae-miR6201 and potential small RNA-mediated mechanisms associated with cadmium accumulation were identified by summarizing specific microRNA profiling patterns and their respective target genes. At the level of wheat roots and leaves, differentially expressed small RNAs related to cadmium accumulation in different plant tissues (roots or leaves) were identified, and functional enrichment analyses on target genes of differentially expressed miRNAs in low- and high-cadmium-accumulating wheat cultivars in different plant tissues (roots or leaves), obtained some known mature miRNAs and new miRNAs. The identified miRNA will be regarded as potential screening biomarkers for low-cadmium accumulation wheat.